2019
DOI: 10.1177/0262728019872038
|View full text |Cite
|
Sign up to set email alerts
|

School Teachers in Rural Bhutan: Quality of Work Life, Well-Being and the Risks of Resignation

Abstract: In Bhutan, recent increases in annual teacher attrition rates, particularly in rural areas, pose significant challenges for the government and concerned agencies in terms of retaining qualified teachers and reducing teacher attrition rates and turnover. This article, partly based on a field study exploring the quality of work life (QWL) and well-being of school teachers in rural Bhutan, explores the possible reasons why such teachers might seek to resign. Using mixed methodology, the study reveals poor QWL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A further challenge that teacher-participants faced while teaching online was associated with students’ disinterest in learning, a familiar problem in Bhutan, raised subtly by Dorji et al (2019: 279). Teacher-participants pointed out that most students, even those who owned smartphones and other gadgets through which they could communicate, were not paying attention to learning.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A further challenge that teacher-participants faced while teaching online was associated with students’ disinterest in learning, a familiar problem in Bhutan, raised subtly by Dorji et al (2019: 279). Teacher-participants pointed out that most students, even those who owned smartphones and other gadgets through which they could communicate, were not paying attention to learning.…”
Section: Resultsmentioning
confidence: 99%
“…Especially those parents who are not literate and sustain their living through farming might have a different perspective of the value of education. In this context, Dorji et al (2019: 281) observed that the educational background of parents seems to play an important role in nurturing resentment of teacher’s efforts to improve local children’s education. It was noted in our study, too, that children with uneducated parents are less likely to become educated because non-educated parents often fail to appreciate the benefits of education.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the same study reveals that adopting promotion and support policies for teacher retention favors the reduction of diseases [23,24]. Some studies, for example, have shown a strong link between QoWL and burnout [25], stress management [26], well-being and resignation risks [27], the organizational climate [28,29], creativity of teachers [28], and the integration of the teacher's life project in the institution, even if they are in unfavorable working conditions [23]. Furthermore, it was evidenced that organizational health and employment status can modify the impact of QoWL [30].…”
Section: Introductionmentioning
confidence: 97%